The Effect of Inflation and Interest Rates on Study Stock Prices at Kompas 100 Companies Index in the Covid-19 Period. - fitriaty fitriaty (Dinasti International Journal of Education Management And Social Science, 2023)
This study aims to examine the effect of inflation and interest rates on stock prices in companies that are members of the Kompas100 index during the Covid-19 pandemic period. This research is a type of quantitative research using regression with the help of SPSS 25.0. The sample for this research is a company that is part of the Kompas 100 Index. This research finds that inflation and interest rates simultaneously have an effect on the price of one share. Based on the partial test, inflation has a positive effect on the Kompas100 company's stock price, while interest rates have a significant negative effect on the Kompas100 company's stock price during the Covid-19 pandemic. The results of this study can be used as a reference for investors to consider inflation and interest rates in making investment decisions and in making regulations.